MAIT cells protect against sterile lung injury - Zhang, X; Li, S; Lason, W; Greco, M; Klenerman, P; Hinks, T (Cell Press, 2025)
Mucosal-associated invariant T (MAIT) cells, the most abundant unconventional T cells in the lung, can exhibit a wide range of functional responses to different triggers via their T cell receptor (TCR) and/or cytokines. Their role, especially in sterile lung injury, is unknown. Using single-cell RNA sequencing (scRNA-seq), spectral analysis, and adoptive transfer in a bleomycin-induced sterile lung injury, we found that bleomycin activates murine pulmonary MAIT cells and is associated with a protective role against bleomycin-induced lung injury. MAIT cells drive the accumulation of type 1 conventional dendritic cells (cDC1s), limiting tissue damage in a DNGR-1-dependent manner. Human scRNA-seq data revealed that MAIT cells were activated, with increased cDC populations in idiopathic pulmonary fibrosis patients. Thus, MAIT cells enhance defense against sterile lung injury by fostering cDC1-driven anti-fibrotic pathways.